State-resolved reactivity and bond-selective control of methane on Ni(111). - Chen, Nan. (2017)
Abstract: State-resolved reactivity is particularly useful to uncover the energy flow details in gas-surface reactions. Here, we combine supersonic molecular beam techniques and laser excitation to characterize the mode- and bond-specific reactivity of methane on a Ni(111) surface. Our results reveal important details about the effect of vibrational mode and symmetry on the reactivity of this benchmark gas-surface reaction. We first introduce a theoretical model of the state-resolved reactivity of methane on a Ni(111) surface. This model provides a theoretical approach to understanding the reactivity of selected vibrational states. More importantly, it can provide an accurate approach to measure the reactivity of methane in vibrational ground state. This approach relies on a detailed knowledge of the vibrational structure of methane, its vibrational cooling dynamics in a supersonic expansion, and understanding of how individual vibrational states contribute to the overall reactivity. In Chapter IV, we introduce a new scheme to measure the state-resolved reactivity based on the `King and Wells' method. With the new detection scheme, we are able to measure reactivity with and without laser excitation simultaneously. In addition, we are able to probe real-time reactivity during the reaction. This method will not only largely reduce the experimental time, but also extend our measurements of state-resolved reactivity to a wider range, which is impossible to measure by post-dose methods. In Chapter V, we explore the state-resolved reactivity of CH4 prepared in a combined bending state (ν2 + ν4) on Ni(111). Our results provide the first comparison between a bend and stretch vibrational state in the same polyad. By this comparison, we confirm the trend that stretching vibrations have better efficiency in promoting reactivity than bending vibrations. In addition, comparing with the 3ν4 state, we provide experimental evidence supporting the theoretical calculation that the ν2 bend state is less efficient than the ν4 bend state in promoting CH4 activation on Ni(111). In the last chapter, we explore the bond- and mode-selectivity of CH2D2 dissociation on Ni(111). Unlike CH4 on Ni(100), our results show that different C-H vibrations bring almost identical enhancement to the overall reactivity of CH2D2 on Ni(111). Through comparisons, we also find surface temperature is more important in a energy-starving region than vibrational modes or symmetries in promoting CH2D2 activation. In addition, we compare our results with the overtone stretching excitation of CH2D2 in gas-phase and gas-surface reactions. The results show that ν1 and ν1 C-H vibrations are less localized than their overtone states in CH2D2 molecules. Our results further uncover details of the role that vibrations play in the bond-selective dissociation of CH2D2 on Ni(111).; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Chemistry.; Advisor: Arthur Utz.; Committee: Charles Sykes, Mary Shultz, and Ricardo Metz.; Keywords: Physical chemistry, Chemistry, and Physics.